Balloon Pulmonary Valvuloplasty with Mammoth Balloon - Adhikari, Chandra Mani; Manandhar, Riju; Acharya, Anjana; Shahi, Ravi; Kansakar, Subodh Bir Singh (Journal of Nobel Medical College, 2026)
Balloon pulmonary valvuloplasty is standard therapy for pulmonary stenosis. The procedure can be done with different balloon catheter. We report a Balloon pulmonary valvuloplasty with the Mammoth balloon in an adult with severe pulmonary stenosis. The device showed good trackability, stability, and rapid inflation. Mammoth balloon appears effective, though larger studies are needed to confirm long-term outcomes